An expanded role for in vitro symbiotic seed germination as a conservation tool: two case studies in North America (Platanthera leucophaea and Epidendrum nocturnum) - Massey, Emily; Zettler, Lawrence (Lankesteriana: International Journal on Orchidology, 2015)
Interest in using mycorrhizal fungi to cultivate orchids from seed in vitro (=symbiotic seed germina- tion) has intensified in recent years and this approach is now an important conservation tool worldwide. In North America, symbiotic germination has been attempted for a growing number of orchid species in peril as a means to acquire seedlings suitable for reintroduction.